2020
DOI: 10.21203/rs.3.rs-54157/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hypoxia-induced Tie1 Drives Stemness and Cisplatin Resistance in Non-small Cell Lung Carcinoma Cells

Abstract: Background: Drug resistance and metastasis involving hypoxic tumor environment and persistent stem cell populations are detrimental to the survival of patients with non-small cell lung carcinoma (NSCLC). Tie1 is upregulated in hypoxia and is believed to counteract the effectiveness of platinum agents, by promoting the stemness properties in cells. We have investigated the association of Tie1 with HIF-1α and cisplatin resistance in NSCLC cell lines. Methods: Expression of Tie1 in a pulmonary microvascular endot… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In turn, YAP in HCC cells activates the AKT/Mechanistic target of rapamycin (mTOR)/sterol regulatory element-binding protein 1 (SREBP1) pathway which accelerates HCC cell growth by lipogenesis induction [70]. Another neoplastic condition in which hypoxia appears to support tumor stemness and drug resistance is non-small-cell lung carcinoma, in which the hypoxic state contributes to confer cisplatin resistance by overexpressing Tie1 in a HIF-1α-dependent way [67]. This mechanism of crosstalk between hypoxic tumor environment and neoplastic stem cells could also serve as a target for the new treatments.…”
Section: Hypoxia and Stem Cellsmentioning
confidence: 99%
“…In turn, YAP in HCC cells activates the AKT/Mechanistic target of rapamycin (mTOR)/sterol regulatory element-binding protein 1 (SREBP1) pathway which accelerates HCC cell growth by lipogenesis induction [70]. Another neoplastic condition in which hypoxia appears to support tumor stemness and drug resistance is non-small-cell lung carcinoma, in which the hypoxic state contributes to confer cisplatin resistance by overexpressing Tie1 in a HIF-1α-dependent way [67]. This mechanism of crosstalk between hypoxic tumor environment and neoplastic stem cells could also serve as a target for the new treatments.…”
Section: Hypoxia and Stem Cellsmentioning
confidence: 99%
“…Under hypoxia, the expression level of hypoxia-inducible factor-1 (HIF-1), which plays a significant role in promoting cancer cell proliferation as well as metastasis, continuously increases. 19,20 In a previous study, the HIF-1α subunit was found to be highly expressed in NSCLC, and its high expression was associated with poor prognosis in NSCLC subjects. 21 Nevertheless, the influence of ITCH and TXNIP on NSCLC requires further investigation.…”
Section: Introductionmentioning
confidence: 95%
“…Hypoxic conditions in local tissues may be caused by tumor growth, energy metabolism, invasion, or incomplete local blood vessels. Under hypoxia, the expression level of hypoxia‐inducible factor‐1 (HIF‐1), which plays a significant role in promoting cancer cell proliferation as well as metastasis, continuously increases 19,20 . In a previous study, the HIF‐1α subunit was found to be highly expressed in NSCLC, and its high expression was associated with poor prognosis in NSCLC subjects 21 .…”
Section: Introductionmentioning
confidence: 99%